2014
DOI: 10.1016/j.aeue.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of the 2D planar metamaterial structure

Abstract: The performance of a 2D metamaterial (MTM) structure using finite element method (FEM) and transmission line model (TLM) is investigated in this paper. The size of the proposed unit cell is 4 mm × 4 mm to resonant around 12 GHz. The unit cell is constructed from a patterned patch and solid ground plane that are connected with via through an FR-4 substrate. The unit cell is characterized from 11 GHz to 14 GHz in terms of S-parameters, effective refractive index, and dispersion properties. It is found that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…The main objective of the cloaking is to reconstruct the phase front of the incident electromagnetic waves after passing the object to be cloaked . To achieve that, the incident wave has to spend an equal time inside the cloak as it takes to pass an object in the free space . Consequently, if the reflective index of the proposed unit cell is less than unity, the phase velocity would be greater than the speed of light in the free space.…”
Section: Rbf Performance and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of the cloaking is to reconstruct the phase front of the incident electromagnetic waves after passing the object to be cloaked . To achieve that, the incident wave has to spend an equal time inside the cloak as it takes to pass an object in the free space . Consequently, if the reflective index of the proposed unit cell is less than unity, the phase velocity would be greater than the speed of light in the free space.…”
Section: Rbf Performance and Discussionmentioning
confidence: 99%
“…24 To achieve that, the incident wave has to spend an equal time inside the cloak as it takes to pass an object in the free space. 25 Consequently, if the reflective index of the proposed unit cell is less than unity, the phase velocity would be greater than the speed of light in the free space. It is found that the proposed RBF based on a single unit cell shows a zero refractive index at 4 GHz.…”
Section: Rbf Performance and Discussionmentioning
confidence: 99%
“…The proposed EBG structures exhibit a capacitive behavior [22], so work as a high-pass filter that allows passing the high frequencies and prevent lower bands. On the other hand, each unit cell can be considered unbalanced circuit because of the inductive absence where the influence of capacitive reactance on the EBG width is higher than its length for the surface current.…”
Section: Ebg Analysis and Performance Studymentioning
confidence: 99%
“…While, metamaterials (MTMs) possess several attractive features such as surface wave reduction and unique stopbands . However, resonant MTM structures suffer from two fundamental limitations: narrow bandwidth over which the desired properties occur and losses due to the conducting inclusions . Miniaturized antennas made from fractal‐shaped space filling MTM curves were proposed in Elwi with enhanced bandwidths.…”
Section: Introductionmentioning
confidence: 99%